Gastrointestinal parasite fauna of nine gentoo penguin chicks (Pygoscelis papua) found dead in an antarctic territory protected zone. Fauna parasitaria gastrointestinal en polluelos de Pingüino Papua (Pygoscelis papua) encontrados muertos en zona antártica - Fredes Martínez, Fernando; Raffo Carvajal, Eduardo; Muñoz Alvarado, Pamela; Herrera, Marcela (Sociedad Chilena de Parasitologia, 2006)
In the present communication, the presence of Streptocara spp. (Nematoda: Acuariidae) and Contracaecum spp. (Nematoda: Anisakidae) in stomach; two scolex of tapeworms (Cestoda: Cyclophyllida) and eggs of Tetrabothrium spp. (Cestoda: Pseudophyllida) in guts of Gentoo penguin chicks found dead in a protected zone of the Antarctic territory is reported